Threadbare BUT Bonded—Weaving Stories and Experiences Into a Collective Quilt of Black Women’s Leadership - Curtis, Sharon (Frontiers in Education, 2020)
Abstract As black women leaders within the 21st century sharing our stories, reflections and contributions remain an area of high anxiety, reluctance and resistance. The fear of these contentions can elicit feelings of invisibility, voicelessness, rejection and reprisal. Black women’s experiences of leadership are, at times, visualised metaphorically as a single bare thread. A thread that manoeuvres and meanders aimlessly, not through choice, but by navigating their way through institutional systems. Their journeys are fuelled with micro aggressions, convoluted racial barriers and systemic obstacles placed within their paths while attempting to reach and sustain their leadership positions. In this research (Curtis, 2014; 2017), has sought to connect these threadbare yet bonded experiences by weaving their counter-narratives into a collective quilt. A quilt designed and developed to show their stories of leadership. This methodology displays their strengths and commands visibility while displaying vibrant, passionate social justice leadership within these symbolic colourful, tired and tangled yarns. Black women’s survival in leadership positions is often not one of centrality within the mainstream literature. These experiences are not commonly championed or celebrated by those who hold dominance within society. However, within this research, black women’s survival is one in which their resilience hangs solitary at times by a threadbare yarn. Using these threads to authenticate connectedness and weaving their journeys of leadership has utilised a bond and created an opportunity to share with other black women leaders their often isolated experiences. The research expands their expressive, creative liberation using the lens of Critical Race Theory to explore the women’s cultural identities as educational leaders. KEYWORDS: Social Justice Leadership, Critical Race Theory, Black feminism, Collective identity